2011
DOI: 10.1007/s00894-011-1307-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking of 2-(benzimidazol-2-ylthio)-N-phenylacetamide-derived small-molecule agonists of human formyl peptide receptor 1

Abstract: Human N-formyl peptide receptor 1 (FPR1) is a G protein-coupled receptor (GPCR) involved in host defense and sensing cellular damage. Since structure-based ligand design for many GPCRs, including FPR1, is restricted by the lack of experimental three dimensional structures, homology modeling has been widely used to study GPCR-ligand binding. Indeed, receptor-ligand binding mode predictions can be derived from homology modeling with supporting ligand information. In the present work, we report comparative dockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Several subpockets of the FPR1 binding site, including two channels ( A and C ), two cavities ( B and E ), and the bottom ( D ) were recently described for this model [43], and the same designation of the subpockets ( A-D ) is used here for comparison (Figure 6B). To determine if these subpockets could accommodate the FPR1 antagonist pharmacophore, receptor-docking poses of compound 10 were determined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several subpockets of the FPR1 binding site, including two channels ( A and C ), two cavities ( B and E ), and the bottom ( D ) were recently described for this model [43], and the same designation of the subpockets ( A-D ) is used here for comparison (Figure 6B). To determine if these subpockets could accommodate the FPR1 antagonist pharmacophore, receptor-docking poses of compound 10 were determined.…”
Section: Resultsmentioning
confidence: 99%
“…According to our docking study, the pharmacophore area I with hydrophobic area III are located near the bottom D of the FPR1 binding site, the protrusion is fitted in cavity B , and area II is located in cavity E with the long hexyl chain positioned in channel C (Figure 6B). FPR1 residues corresponding to these areas of the binding pocket were enumerated previously [43]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous mutagenesis and ligand-docking studies of FPR (Fujita et al 2011;Khlebnikov et al 2012;Mills et al 2000) have revealed that the amino acid residues constituting the ligand-binding pocket form two cavities located inside the transmembrane domains. There were 10 amino acid residues proposed as the sites critical for ligand binding in the FPR1: F102, V105, D106, L109, R205, F206, W254, Y257, S287, and F291 (Fujita et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are examples of what appear to be small structural modifications that change a ligand from a target-selective functionality to a nonselective functionality against FPR1 and FPR2. For instance, Khlebnikov et al (2012) report that by modifying the p-COOCH 3 group on their benzimidazole selective FPR1 agonist (AG-11/05) to a m-COCH 3 group, they obtained the dual FPR1/FPR2 agonist (AG-11/06). In a similar manner, we observed that the modification of the phenol portion of the R 2 functionality of the FPR2 selective antagonist (1754-20) to a methyl group yielded the dual FPR1/FPR2 antagonist (1754-26) ( Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%